The Relationship Between Chest Imaging Findings and the Viral Load of COVID-19 - Zhao, Wei; He, Lei; Tang, Haoneng; Xie, Xingzhi; Tang, Lingli; Liu, Jun (Frontiers in Medicine, 2020)
Abstract Purpose: We aimed to investigate the relationship between clinical characteristics, radiographic features and the viral load of patients with coronavirus disease 2019 (COVID-19). Methods and Materials: We retrospectively collected 56 COVID-19 cases from two institutions in Hunan province, China. The basal clinical characteristics, detail imaging features and follow-up CT changes were evaluated and the relationship with the viral load was analysed. Results: GGO (48, 85.7%), vascular enlargement (44, 78.6%) were the most frequent signs in COVID-19 patients. 64.3% of the margins of the lesions were uneasily differentiated. However, no significant correlations were found in terms of leucocytes, neutrophils, lymphocytes, platelets and C-reactive protein (all P>0.05). In contrast, the uneasily differentiated margin was negatively correlated with the Ct value (r=-0.283, P=0.042), that is, an uneasily differentiated margin indicated a lower Ct value (P=0.043). Patients with a lower Ct value were likely to present a progress follow-up change (P=0.022). The Ct value at baseline could predicted a progress follow-up change with an AUC of 0.685 (Cut-off value=29.48). All the 4 with normal CT findings presented new lesion(s) on follow-up CT scans. Conclusion: The viral load of COVID-19 is negatively correlated with an uneasily differentiated lesion margin on initial CT scan images and the Ct value should be paid attention to in making the diagnosis. In addition, following-up CT scans is necessary for patients with normal CT at initial diagnosis, especially for those with a low Ct value.